Emerging roles of circular RNAs in systemic lupus erythematosus - Wang, Xin (Mol Ther Nucleic Acids, 2021)
Circular RNAs (circRNAs) are a class of non-coding RNAs with covalently closed single-stranded structures lacking 5′–3′ polarity and a polyadenine tail. Over recent years, a growing body of studies have been conducted to explore the roles of circRNAs in human diseases. Systemic lupus erythematosus (SLE) is a severe autoimmune disorder characterized by the presence of autoantibodies and excessive inflammation, which impact multiple organs. Recent advances have begun to shed light on the roles of circRNAs in SLE, providing fresh insights into the pathogenesis of SLE and the latent capacity for translation into clinical applications. Here, we briefly introduce these “star molecules” and summarize their roles in SLE. In addition, we outline the limitations of the current studies and raise prospects for future research.